Denitrification of a landfill leachate with high nitrate concentration in an anoxic rotating biological contactor - Cortez, Susana (2011)
The denitrification performance of a lab-scale anoxic rotating biological contactor (RBC) using landfill leachate with high nitrate concentration was evaluated. Under a carbon to nitrogen ratio (C/N) of 2, the reactor achieved N-NO3 − removal efficiencies above 95% for concentrations up to 100 mg N-NO3 − l−1. The highest observed denitrification rate was 55 mg N-NO3 − l−1 h−1 (15 g N-NO3 − m−2 d−1) at a nitrate concentration of 560 mg N-NO3 − l−1. Although the reactor has revealed a very good performance in terms of denitrification, effluent chemical oxygen demand (COD) concentrations were still high for direct discharge. The results obtained in a subsequent experiment at constant nitrate concentration (220 mg N-NO3 − l−1) and lower C/N ratios (1.2 and 1.5) evidenced that the organic matter present in the leachate was non-biodegradable. A phosphorus concentration of 10 mg P-PO4 3− l−1 promoted autotrophic denitrification, revealing the importance of phosphorus concentration on biological denitrification processes.